A new imidazole alkaloid and other constituents from Pilocarpus grandiflorus and their antifungal activity - De Souza, Rejane C.; Fernandes, João B.; Vieira, Paulo C.; Da Silva, M. Fátima Das G. F.; Godoy, Marizete F. P. [UNESP]; Pagnocca, Fernando C. [UNESP]; Bueno, Odair C. [UNESP]; Hebling, M. José A. [UNESP]; Pirani, José R. (My University, 2005)
The stems of Pilocarpus grandiflorus have afforded the new imidazole alkaloid 4,6-dehydro-1,2,4,5-tetrahydro-2,5-dioxopilocarpine in addition to the 17 known compounds germanicol, β-amiryn, ocotillone, stigmast-4-en-3-one, 3β-hydroxy-stigmast-5-en-7-one, 6β-hydroxy-stigmast-4-en-3-one, β-sitosterol, scopoletin, 3-(1′,1′-dimethylallyl)-scopoletin, elisin, dictamine, 4-methoxy-2-quinolone, platydesmine, syringaresinol, syringaldehyde, syringic acid and vanillic acid. Their structures were elucidated on the basis of chemical and spectroscopic evidence. The phenolic compounds vanillic acid and syringaldehyde and the furoquinoline alkaloid platydesmine exhibited antifungal activity against Leucoagaricus gongylophorus, the symbiotic fungus of leaf-cutting ants (Atta sexdens rubropilosa). © 2005 Verlag der Zeitschrift für Naturforschung.
Keywords: Atta sexdens rubropilosa; Imidazole Alkaloid; Jaborandi; Leucoagaricus gongylophorus; Pilocarpus grandiflorus